PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING STUDI KASUS PT ASSHIDIQ CATER INDONESIA - Muhammad Ichwan hamzah; Lili Supriyadi; Afried lazuardi (Jurnal Ekonomi Bisnis Indonesia, 2021)
The purpose of this study to determine the influence of the style of leadership, compensation, and job environment on employee performance and job satisfaction on PT Asshidiq Cater Indonesia. The population in this study are all employees of PT Asshidiq Cater Indonesia. The method used is descriptive method with quantitative approach. Based on the research conclusions show leadership styles have a significant impact on job satisfaction, compensation has a significant influence on job satisfaction, job environment has a significant effect on job satisfaction, job satisfaction has a significant influence on employee performance, leadership style does not have a significant influence on employee performance, the working environment has an influence on employee performance.